Light-chain cardiac amyloidosis with neuropathy: a case report - Xu ZW (Dove Medical Press, 2015)
Zhan-Wen Xu,1 Ya-Qin Li,1 Li-xia Liu,2 Bing-Juan Zhou3 1Department of Cardiology, 2Department of Ultrasound, Affiliated Hospital of Hebei University, 3Department of Pathology, Baoding First Central Hospital, Baoding, People’s Republic of China Abstract: Light-chain amyloidosis is a relatively rare multisystem disorder. The disease often is normally difficult to diagnose due to its broad range of characters without specific symptoms. A 62-year-old male patient presented with heart failure after experiencing a long period of unexplained and untreated gastrointestinal symptoms. Clinical examination and laboratory findings indicated a systemic process with cardiac involvement. Echocardiography revealed concentric left ventricular hypertrophy with enhanced echogenicity and preserved ejection fraction. Rectum biopsy confirmed amyloid deposition. The side effect of delayed diagnosis on prognosis and the appropriate diagnostic strategy has been discussed. Keywords: light-chain amyloidosis, cardiac amyloidosis, echocardiography, autonomic neuropathy, peripheral neuropathy